DETERMINATION OF WATER REQUIREMENTS AND IRRI-GATION SCHEDULING FOR DATE PALM OFFSHOOT - A Al-Humaid; Kassem M.A. (Arab Universities Journal of Agricultural Sciences, 2005)
The current study was carried out at the Agricultural and Veterinary Research Station, Faculty of Agriculture and Veterinary Medicine, Qassim University, Kingdom of Saudi Arabia during the two seasons 2003/2004 and 2003/2004. The objectives of this study are to investigate the effect of irrigation scheduling methods with different amounts of applied water on date palme offshoot growth, Determination offshoot consumptive use, crop coefficient, actual water requirements and the suitable soil moisture tension in the root zone before irrigation. The irrigation was scheduling by three methods, evapotranspiration calculation method, soil moisture depletion  method and farmer method (control). The evapotranspiration  calculation method (ETo) included ten treatments as a percentage of evapotranspiration (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 ETo). The soil moisture depletion method included five treatments of soil moisture depletion as a percentage of field capacity (50%Fc, 60%Fc, 70% Fc, 80% Fc and 90% Fc). The results showed that scheduling irrigation of the offshoot by evapotranspiration calculation method (ETo) or by soil moisture depletion  method, the amount of applied water decreased and the offshoot growth and the water use efficiency increased; compared with the farmer scheduling method. The daily and seasonal gross irrigation requirements for date palm offshoots were 51.3 l/day and 2191 m3/hec.year, while the farmer applied 19960 m3/h.year. So, the farmer added seven times as much as the actual gross irrigation requirements. The maximum water use efficiency were 2.5 kg/m3 and 1.44 kg/m3 for the treatments 0.1 ETo and 50% Fc, respectively. The suitable soil  moisture tension in the root zone before irrigation were 21.5  to 22 C-bar and 22.5 to 23 C-bar for 60 cm and 90 cm depths, respectively.